Kebijakan Redaksional Gopos.id Dalam Produksi Berita Pemilihan Presiden 2024 - Mamula, Oktavira; dano Putri, citra F.I.L; Mursalim, Muhammad (JAMBURA JURNAL ILMU KOMUNIKASI, 2024)
The editorial policy serves as a guideline for the editorial team as a reference in managing the publication of news content. The research problem is how the editorial policy is implemented by the online media Gopos.id in producing news on the 2024 presidential election. This research uses the descriptive qualitative method, alongside with the data collection techniques such as observation, interviews, documentation, and literature study. To examine the editorial policy implemented by Gopos.id in the production of news on the 2024 presidential election, the researcher uses the setting theory. The research results show that in safeguarding the democratic process, particularly the 2024 Presidential Election, Gopos.id implements several policies at each stage of news production. Gopos.id concerns the relevance of the news, the popularity of current issues, and conducts comparative studies as part of their approach. In order to ensure comprehensive coverage related to the 2024 presidential election, Gopos.id has established a specific policy that assigns journalists to each presidential candidate pair